Partial response to dabrafenib and trametinib in relapsed BRAF V600E-Mutated multiple myeloma and possible mechanisms of resistance. Issue 4 (8th April 2022) - Ernst, Tina; Aebi, Stefan; Zander, Andrea; Zander, Thilo
Abstract : BRAF V600E mutations are detected in 3%–10% of patients with multiple myeloma (MM) and are associated with more aggressive disease, higher frequency of extramedullary growth and shorter survival. Monotherapy with the BRAF inhibitor vemurafenib has been disappointing in MM. In patients with BRAF-mutated melanoma, MEK and BRAF inhibition has been a successful approach. Here we describe a very good partial response and possible mechanisms of resistance to a combination of the BRAF inhibitor dabrafenib and the MEK inhibitor trametinib in a patient with BRAF V600E-mutant refractory MM.